Moderating Effect of Tax Audit Probability on the Causality Between Taxpaying Attitudes and Tax Compliance Behaviour in Restaurants of Uasin Gishu County (Kenya) - Kimitei, Edwin; Kiprono, Eric; Sang, Jane (DINASTI RESEARCH, 2024)
We investigated the moderating influence of audit probability on the effect of taxpaying attitudes on tax compliance behaviour in restaurants in Kenya. Four linear regression models were compared. Estimations in the models suggest that taxpayers’ attitudes and audit probability have significant effects on the tax compliance of the restaurants, but the influence of external audit probability is more significant. Estimations in model where taxpaying attitudes without the moderating influence of audit probability exerted a significant effect on tax compliance by 22%, while taxpaying attitudes with the moderating influence of audit probability exerted 27%. Taxpaying attitudes with the moderating influence of the external audit probability dimension had a more significant contribution to the changes in tax compliance. The findings demonstrated that if taxpayers’ attitudes improved and audit probability was leveraged by the tax authorities, tax compliance behaviour of restaurants would be improved for restaurant owners in Kenya.